2012
DOI: 10.1200/jco.2011.41.2528
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Mapping and Sentinel Lymph Node Biopsy in Women With Squamous Cell Carcinoma of the Vulva: A Gynecologic Oncology Group Study

Abstract: A B S T R A C T PurposeTo determine the safety of sentinel lymph node biopsy as a replacement for inguinal femoral lymphadenectomy in selected women with vulvar cancer. Patients and MethodsEligible women had squamous cell carcinoma, at least 1-mm invasion, and tumor size Ն 2 cm and Յ 6 cm. The primary tumor was limited to the vulva, and there were no groin lymph nodes that were clinically suggestive of cancer. All women underwent intraoperative lymphatic mapping, sentinel lymph node biopsy, and inguinal femora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
232
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(255 citation statements)
references
References 16 publications
3
232
0
7
Order By: Relevance
“…The GROINS V and the GOG study reported the safety of the SLN biopsy in selected women with vulvar cancer (23,63). In the study of the GOG, women with squamous cell cancer of the vulva were eligible if the depth of invasion was at least 1 mm, the tumor was limited to the vulva, the primary tumor size was at least 2 cm and not larger than 6 cm and there were not any groin lymph nodes clinically suspicious for metastases.…”
Section: Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…The GROINS V and the GOG study reported the safety of the SLN biopsy in selected women with vulvar cancer (23,63). In the study of the GOG, women with squamous cell cancer of the vulva were eligible if the depth of invasion was at least 1 mm, the tumor was limited to the vulva, the primary tumor size was at least 2 cm and not larger than 6 cm and there were not any groin lymph nodes clinically suspicious for metastases.…”
Section: Incidencementioning
confidence: 99%
“…In the study of the GOG, women with squamous cell cancer of the vulva were eligible if the depth of invasion was at least 1 mm, the tumor was limited to the vulva, the primary tumor size was at least 2 cm and not larger than 6 cm and there were not any groin lymph nodes clinically suspicious for metastases. Women underwent SLN biopsy and inguinal femoral lymphadenectomy, the sensitivity was 91.7% and the falsenegative rate was 3.7% (63).…”
Section: Incidencementioning
confidence: 99%
“…As presented here, all patients with lymph node metastases died and had a significantly shorter survival compared to women without lymph node metastases. Two large studies revealed that sentinel node procedures can be performed in women presenting with a unifocal disease, a tumour size below 4 cm and clinically negative lymph nodes [11,12]. All cases but one in this study had tumour sizes exceeding 5 cm, and five women had clinically enlarged lymph nodes, with two women revealing no metastases in the final histology report.…”
Section: Discussionmentioning
confidence: 59%
“…Despite these more conservative surgeries, significant morbidity has persisted. Although wound complications are generally short-lived, lymphedema is a chronic problem which requires long-term management (4). Recently, sentinel lymph node (SLN) biopsy has been introduced as an alternative in order to adequately assess for regional lymph node metastasis and to avoid the morbidity of complete inguinofemoral lymphadenectomy.…”
Section: Introductionmentioning
confidence: 99%